Implicações do choque de gestão e reformas em Minas Gerais: a avaliação de desempenho individual (ADI) dos docentes da rede estadual de ensino de Uberlândia no período 2003/2010 - Gouveia, Cíntia D´ângelo da Silva (2012)
This study was developed in the master s program from Universidade Federal de Uberlândia (UFU) on the field State, Policy and Management Education. It has as goal to analise the (re)definition of the role of the State and the changes of the public management from Minas Gerais (MG) State. Therefore, it was taken as methodology a literature and documental review of the subjects proposed in this study, also an analysis of official government documents. In the study, it is specially analyzed the State and the educational Policies developed during both terms of Aécio Neves as governor of Minas Gerais, the research seeks to understand the assumptions of the implemented reform; the purposes of the management and their instruments through the Choque de Gestão Program. It was focused in the study the process of the implementation of the Individual Performance Evaluation (IPE) of the Education employees from public schools of MG in Uberlândia city, under the logic of the new public management called managerial as an economical, social, political strategy. A qualitative research was developed by applying open questionnaires from the visit to five public schools of Uberlândia city (MG). It is analyzed in a subjective way, among the actors, the prospects of implementing and developing the IPE in the schools and how it has influenced the day-to-day teaching practice of education professionals.